2019
DOI: 10.1002/jbmr.3825
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Bone Vascular Network is Sexually Dimorphic

Abstract: Osteoblast (OB) lineage cells are an important source of vascular endothelial growth factor (VEGF), which is critical for bone growth and repair. During bone development, pubertal differences in males and females exist, but little is known about whether VEGF signaling contributes to skeletal sexual dimorphism. We have found that in mice, conditional disruption of VEGF in osteocalcin‐expressing cells (OcnVEGFKO) exerts a divergent influence on morphological, cellular, and whole bone properties between sexes. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 47 publications
6
54
0
Order By: Relevance
“…Both Lama1 and Mmp9 expression exhibited greater upregulation in male than in female OBVEGFKO cells. In particular, elevated levels of MMP9 correlate with osteoporotic bone loss ( Haibo et al, 1997 ), and, given the function of MMP9 in matrix remodelling, these findings indicate possible pathological remodelling effects that could, in part, be responsible for the aberrations in matrix microarchitecture and vascular anomalies in the male OcnVEGFKO bones ( Goring et al, 2019 ). Contrasting with these effects, differential changes in the expression of Hc and Itgae were detected following OBVEGFKO in male and female OBs.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Both Lama1 and Mmp9 expression exhibited greater upregulation in male than in female OBVEGFKO cells. In particular, elevated levels of MMP9 correlate with osteoporotic bone loss ( Haibo et al, 1997 ), and, given the function of MMP9 in matrix remodelling, these findings indicate possible pathological remodelling effects that could, in part, be responsible for the aberrations in matrix microarchitecture and vascular anomalies in the male OcnVEGFKO bones ( Goring et al, 2019 ). Contrasting with these effects, differential changes in the expression of Hc and Itgae were detected following OBVEGFKO in male and female OBs.…”
Section: Discussionmentioning
confidence: 98%
“…Uniquely, these techniques have enabled the in-depth assessment and characterisation of nanoscale sex differences in matrix composition following the loss of VEGF. Previous studies linked the loss of VEGF to bone pathology characterised by a profound osteoporotic phenotype present following the deletion of Vegf in early and late-stage OBs ( Goring et al, 2019 ; Liu et al, 2012 ). Furthermore, clinical reports have also identified that the loss of VEGF is associated with the degenerative bone loss seen in osteoporosis ( Senel et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations